Current Perspectives of Prenatal Cell-free DNA Screening in Clinical Management of First-Trimester Septated Cystic Hygroma - Sherer DM; Hsieh V; Hall A; Gerren A; Walters E; Dalloul M (Dove Medical Press, 2022)
David M Sherer, Vicky Hsieh, Anika Hall, Allison Gerren, Erin Walters, Mudar Dalloul The Division of Maternal Fetal Medicine, the Department of Obstetrics and Gynecology, State University of New York (SUNY), Downstate Health Sciences University, Brooklyn, New York, USACorrespondence: David M Sherer, Division of Maternal-Fetal Medicine, Department of Obstetrics and Gynecology, State University of New York (SUNY), Downstate Health Sciences University, 450 Clarkson Avenue, Box 24, Brooklyn, NY, 11203, USA, Tel +001-718-270-2081, Fax +001-718-270-4122, Email davidmsherer@gmail.comAbstract: First-trimester septated cystic hygroma occurs in approximately 1 in 268 pregnancies and has long been associated with a markedly increased risk of fetal aneuploidy and, among euploid fetuses, an increased risk of structural anomalies primarily affecting the cardiac and skeletal systems. Invasive prenatal diagnosis - chorionic villus sampling and/or amniocentesis - encompasses the time-honored clinical tools for the next step in management following prenatal sonographic diagnosis of first-trimester septated cystic hygroma. Currently, prenatal cell-free DNA (cfDNA) screening for fetal aneuploidy with select microdeletions is gradually replacing the considerably less sensitive, and labor-intensive combined first-trimester screening. These new technologies have opened potential new venues in the clinical management of this ominous late first-trimester sonographic diagnosis. Advances in cfDNA technologies are now permitting detection of chromosomal copy number variants (CNV) larger than 7Mb across genome and select serious single-gene disorders (mainly impacting skeletal and neurological development), affecting quality of life and may benefit from medical and/or surgical management. This commentary will address the available non-invasive prenatal screening technologies, which clearly enhance immediate genetic analysis modalities applicable in the presence of the complex sonographic finding of first-trimester septated cystic hygroma.Keywords: prenatal ultrasound, first-trimester septated cystic hygroma, cell free DNA, cfDNA, noninvasive prenatal screening (NIPS), transvaginal ultrasound, fetal aneuploidy